A GAMBARAN PENGGUNAAN PEMAKAIAN KONTRASEPSI HORMONAL TERHADAP PENYAKIT KARDIOVASKULAR DI PUSKESMAS NATAI PALINGKAU PERIODE MARET – APRIL 2023: GAMBARAN PENGGUNAAN PEMAKAIAN KONTRASEPSI HORMONAL TERHADAP PENYAKIT KARDIOVASKULAR DI PUSKESMAS NATAI PALINGKAU PERIODE MARET – APRIL 2023 - Anggi Pratiwi (Jurnal Medika Hutama, 2023)
Abstract This research is of the descriptive-analytic type, with the cross-sectional method with the statistic testing of regressive logistic. The monitored are Hypertension; Diabetes mellitus, Hypercholesterolemia, Strokes; and VTE (Venous Thromboembolism) as results of the long-term usage of hormonal contraception methods (more than 10 years). Data revealed from a total of 84 samples, 72 are samples of hormonal contraception devices and 12 without contraception. The results show that hypercholesterolemia is significantly affected by the usage of long-term hormonal contraception (sig value 0,012). This study therefore successfully proves that long-term usage of hormonal contraception does affect cholesterol rates in the blood as a risk factor of cardiovascular diseases. Keyword: Population Growth, Hormonal Contraception, Cardiovascular Diseases.